Identifikasi Faktor Eksternal Terhadap Peran Masyarakat Dalam Pengelolaan Sampah Plastik Pantai Teluk Penyu Cilacap - Nandang Bekti Karnowati; Tri Yuwono (School of Postgraduate Studies, Diponegoro Univer, 2023)
AbstractReduced tourism is one of the unintended consequences of garbage accumulation in popular tourist destinations. There are both internal and external elements that influence people's willingness to participate in managed waste. The purpose of this research is to identify the external elements in the coastal community of Teluk Turtle Cilacap that influence inhabitants' involvement in garbage management. Methods included conducting in-depth interviews with 204 eligible beachgoers in the Teluk Penyu area and collecting data through observation and questionnaires. This research found that 42.1% of the variation in people involvement in controlling Teluk Turtle beach garbage was attributable to five factors: community leaders, information, incentives, local institutional capabilities, and infrastructure. Citizens' engagement in waste management is most directly influenced by incentives and community leaders and least by the local community's access to relevant knowledge, resources, and infrastructure. Unlike the knowledge variable, which can entirely mediate the relationship between community leaders, facilities, and the competency of local institutions and participation, the incentive variable can fully mediate the relationship between facilities and participation. As this research shows, environmental factors have a substantial impact on waste management involvement among Teluk Turtle people. The study's findings can be utilized as a guide for enhancing coastal trash management by highlighting the importance of the relationship between the variables investigated.